Improving efficiency of installation for disposal of oil-contaminated soil at low temperatures - L. O. Shtripling; E. G. Kholkin; V. V. Merkulov (Омский научный вестник)
The article discusses some features of the method of reagent encapsulation in conditions of negative temperatures. An installation layout has been created that makes temperature measurement of the encapsulated material in the process of reagent encapsulation. During the experiment, the duration of maintaining the temperature necessary for preparing the next portion is determined. A comparison is made of the methods for supplying carbon dioxide to the installation during reagent encapsulation. As a result of the experiment, a more profitable way of supplying carbon dioxide to the installation is determined.